REASONS OF CHILDREN’S MISFORTUNE - Baranov Максим Николаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In article some actual aspects of the reasons of children’s misfortune in Kazakhstan are considered.